Pentecostal mission and global Christianity - Wonsuk, Ma; Kärkkäinen, Veli-Matti; Asamoah-Gyadu, J. Kwabena (Regnum Edinburgh centenary series, 2014)
Introduction: Pentecostalism and world mission / editors -- The emergence of a multidimensional global missionary movement: a historical review / Allan Heaton Anderson -- The Pentecostal understanding of mission / Veli-Matti Karkkainen -- You shall receive power: empowerment in Pentecostal/Charismatic Christianity / J. Kwabena Asamoah-Gyadu -- Everything is permissible, but not everything is beneficial (1 Cor. 10:23): Pneumatological Christology of the Parousian Church of Christ and (ab)uses of spiritual power in Nigerian Pentecostalism / Innocent Ogueri Aguwuom -- Pentecostal evangelism, church planting, and church growth / Julie C. Ma -- Church growth: reflections on Yoido Full Gospel Church / Younghoon Lee -- Silver and gold have I none: healing and restoration in Pentecostalism / Elizabeth Salazar Sanzana -- Principalities and powers / Opoku Onyinah -- Ministry of mercy and justice / Johan Mostert -- Christian Unity and Pentecostal mission: a contradiction? / Cecil M. Robeck, Jr. -- Global Christianity and ecumenism in Asian Pentecostalism / Connie Au -- The sevenfold spirit: a Pentecostal approach to Christian theology of religions / Tony Richie -- Pentecostal interaction with religions: a Nepali reflection / Bal Krishna Sharma -- Word, work, and wonder as holistic ministry / Douglas Petersen -- Blessings in Pentecostal theology and mission / Wonsuk Ma -- Church and society: a Pentecostal perspective from the southern hemisphere / Japie La Poorta -- Pentecostals, society and Christian mission in Latin America / Miguel Alvarez -- Could anthropology contribute to the future of Swedish Pentecostalism? / Jan-Ake Alvarsson -- Pentecostal theological education and ministerial formation / Teresa Chai -- Ecology and the future of Pentecostalism: problems, possibilities and proposals / Jonathan W. Rice